Transient Support from Fibroblasts is Sufficient to Drive Functional Vascularization in Engineered Tissues. (25th June 2020) - Song, Hyun‐Ho Greco; Lammers, Alex; Sundaram, Subramanian; Rubio, Logan; Chen, Amanda X.; Li, Linqing; Eyckmans, Jeroen; Bhatia, Sangeeta N.; Chen, Christopher S.
Abstract: Formation of capillary blood vasculature is a critical requirement for native as well as engineered organs and can be induced in vitro by coculturing endothelial cells with fibroblasts. However, whether these fibroblasts are required only in the initial morphogenesis of endothelial cells or needed throughout is unknown, and the ability to remove these stromal cells after assembly can be useful for clinical translation. In this study, a technique termed CAMEO (Controlled Apoptosis in Multicellular Tissues for Engineered Organogenesis) is introduced, whereby fibroblasts are selectively ablated on demand, and it is utilized to probe the dispensability of fibroblasts in vascular morphogenesis. The presence of fibroblasts is shown to be necessary only during the first few days of endothelial cell morphogenesis, after which they can be ablated without significantly affecting the structural and functional features of the developed vasculature. Furthermore, the use of CAMEO to vascularize a construct containing primary human hepatocytes that improved tissue function is demonstrated. In conclusion, this study suggests that transient, initial support from fibroblasts is sufficient to drive vascular morphogenesis in engineered tissues, and this strategy of engineering‐via‐elimination may provide a new general approach for achieving desired functions and cell compositions in engineered organs. Abstract : Inducing endothelial morphogenesis is critical for establishing microvasculature in engineered organs. Current approaches use non‐native fibroblasts as feeder cells within the coculture, which introduces additional challenges for translational applications. Here, CAMEO (Controlled Apoptosis in Multicellular Tissues for Engineered Organogenesis) is introduced to safely eliminate supporting cells from the coculture on demand, leaving behind vascularized, functional, and feeder‐free hepatic tissues.